Concentration of lipids, cholesterol, and fatty acid profile in chicken breast meat affected by wooden breast myopathy frozen for up to 12 mo - Erick Alonso Villegas-Cayllahua; Daniel Rodrigues Dutra; Rodrigo Fortunato de Oliveira; Mateus Roberto Pereira; Érika Nayara Freire Cavalcanti; Fábio Borba Ferrari; Rodrigo Alves de Souza; Heloísa de Almeida Fidelis; Aline Giampietro-Ganeco; Pedro Alves de Souza; Juliana Lolli Malagoli de Mello; Hirasilva Borba (Poultry Science, 2024)
ABSTRACT: The aim of this study was to examine the effects of frozen storage for 12 mo on the concentrations of lipids and cholesterol and fatty acid profile of wooden chicken breast meat. A total of 120 samples of chicken breasts were selected, according to the degree of “wooden breast” myopathy [“severe,” “moderate,” and “normal” (absence of myopathy)], from male chickens slaughtered at 42 d of age, from Cobb 500 strain. Part of the samples (n = 20/grade of severity) were evaluated on the day of collection and the remainder were packaged, frozen and stored at −18°C for up to 12 mo. At the beginning (collection day) and at the end of the proposed freezing period (12 mo), analyses of lipid, cholesterol, and fatty acid profile were carried out. Percentage of saturated (SFA), monounsaturated (MUFA), and polyunsaturated (PUFA) fatty acids were evaluated. Meats affected by wooden breast myopathy had lower levels of PUFA that exert beneficial effects on health, such as DHA, EPA and ARA, and this profile is impaired by prolonged storage (12 mo), which results in important nutritional losses for the consumer.